(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
This article investigates the role of discursive novel formats for the formation of human identity. The focus is on the artistic explication of Soviet-style discourses, the militaristic discourse of violence, anti-imperial humanism, the discourse of individual consciousness, and mythological. It was found out that the polydiscursiveness in the novel by Sergei Zhadan “Internat” is due to the split consciousness of the hero of the novel. The author communicates the creation of an open artistic and psychological space by discussing the problems of national identity and modern statehood in Ukraine. The Soviet discursive format and the aggressive discourse of violence simulate imperial social reality, which is considered by the author as an inhumane social experiment on man and which can not be perceived in the modern democratic world.The author values human values in the process of deploying humanistic discourse, which represents the ideal social model and in which situationally realised responsible, courageous, heroic behaviour of man. Since the discourse of violence provokes a mortal danger situation, the author also actively addresses the mythological discourse, in which the destabilising person is disfigured by a sense of fear and confusion. The discourse of individual consciousness, combined with the mythological, reflects the positive dynamics of I – the character in the direction of identity. The complex interaction of the discourses of individual consciousness and social discourses leads to the nonlinearity of the text space, the shift of time coordinates, which allows to distinguish the philosophical existential discourse as a dominant, which determines the type of character consciousness and the relevance of the text to the literary examples of the era of the second modern.